تأثير نموذج التّعليم Round Table لترقيّة مهارة الكتابة لدى طلاب الفصل الحادي عشر في المدرسة الثّانويّة الإسلاميّة الحكوميّة 4 آغام - Anggraini, Bela; Nurhasnah, Nurhasnah; Rizal, Eka; Yusra, Oktarina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research purpose to determine the effect of the round table learning model on students' writing abilities at MAN 4 AGAM. The researcher found problems in learning Arabic languagee in class XI students at Madrasah Aliyah Negeri 4 Agam. Lack of student interest in teaching Arabic, and found student scores are still below the minimum score obtained. The process of teaching Arabic to students is still boring, because teachers teach using traditional learning models and students only become listeners until they feel bored learning Arabic. This research is quantitative research with experimental research type. The design used was quasi experimental design. The data analysis method used is statistical analysis using the SPSS program. It can be concluded that there is an effect of the Round Table teaching model in improving the ability of writing skills of grade XI students at Madrasah Aliyah Negeri 4 Agam. Then the significance result of the hypothesis tes is 0.00. This result is smaller than 0.05. Therefore, H0 is rejected and the acceptable value of Ha which is the meaning of the Round Table teaching model affects the teaching of writing skills